Summative Assessment Using Moodle Learning Management System in Vocational High School: Teacher Perspective - Kustiaman, Aditya Irfan; Wahyudin, Dinn; Dewi, Laksmi (Universitas Sebelas Maret, 2023)
This study used a qualitative approach using descriptive methods. The research site was conducted at Cimahi City Center for Excellence Vocational High School (Center of Excellence) with teacher research participants in the curriculum and subject teachers involved as supervisors in implementing summative assessments. Data collection is conducted by conducting interviews and documentation studies on learning management systems owned by schools. The validity and reliability of the research results are checked using triangulation of data and information. As a result of the study, summative assessments using LMS Moodle were more effective over time, reduced paper usage was easy to use, and encouraged mastering technology competencies for teachers. The negative impact of using LMS Moodle on summative assessment is the student's chances of finding answers online. Anticipation can be achieved by adding a blocking feature to Moodle. LMS Moodle-based facilities and facilities support facilities are the main prerequisites for the smooth implementation of summative assessments.